Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Pada Usaha AMH Gorden Dan Wallpaper Di Kota Malang - Haris, Ahmad Maulana; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the influence of product quality and price on purchasing decisions for the AMH curtain and wallpaper business in Malang City. The data collection method used in this research used a questionnaire distributed directly in Malang City with a sample size of 75 respondents. The independent variables in this research are Product Quality and Price, while the dependent variable in this research is Purchasing Decisions. The testing stages are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, F test, t test, and R2 coefficient of determination test. The analytical method in this research is Multiple Linear Regression Analysis processed with SPSS 16.0. The results of this research are that product quality and price simultaneously have a positive and significant effect on purchasing decisions. Partially, product quality and price have a significant positive effect on purchasing decisions for the AMH curtain and wallpaper business in Malang City. The adjusted R Square figure in the research is 0.116, this shows that 11.6% of purchasing decision variables can be explained by the Product Quality and Price variables while the remaining 88.4% is influenced by other variables. Keywords: Product Quality, Price, and Purchase Decision